Mekanisme Pertahanan Ego Tokoh Utama Dalam Novel Mendhung Angendanu Karya Budiono Santoso Setradjaja (Kajian Psikoanalisis Sigmund Freud) - Kuni Auliya Rahmah; Darni Darni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The main character has a strong ego so this will be related to the id and superego. But when anxiety arises, the ego must try to be strong against whatever happens. There is an ego defense mechanism carried out by the main character due to the emergence of neurotic anxiety. The aim of this research is to determine the form of ego defense mechanism used by the main character and the form of neurotic anxiety experienced by the main character in the novel Mendhung Angendanu. This research uses a qualitative research method that focuses more on analytical descriptiveness using Sigmund Freud's psychoanalytic theory. The data sources for this research are divided into two, namely primary data sources and secondary data sources. Primary data sources are the main data sources, namely using a Javanese novel entitled Mendhung Angendanu which was published in 2022. And secondary data sources are supporting data sources such as previous research, journals, books that are appropriate to the research topic. The results of this research show that the ego defense mechanisms used by the main character are sublimation, regression, rationalization and repression. This ego defense mechanism is caused by a mental problem in the form of neurotic anxiety, namely hurt, frustration and lack of self-confidence.